Mission to Pluto : the first visit to an ice dwarf and the Kuiper belt - Carson, Mary Kay (Scientists in the field., 2016)
"Follow a spacecraft the size of a piano, named New Horizons, on the first ever spacecraft mission to Pluto, the space entity formerly known as a planet, in the latest addition to the epic and authoritative Scientists in the Field series."--